2017
DOI: 10.3847/1538-4357/835/1/87
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Catalog: Considering the Importance of Carbon, Magnesium, and Neon in the Evolution of Stars and Habitable Zones

Abstract: Building on previous work, we have expanded our catalog of evolutionary models for stars with variable composition; here we present models for stars of mass 0.5 -1.2 M ⊙ , at scaled metallicities of 0.1 -1.5 Z ⊙ , and specific C/Fe, Mg/Fe, and Ne/Fe values of 0.58 -1.72 C/Fe ⊙ , 0.54 -1.84 Mg/Fe ⊙ and 0.5 -2.0 Ne/Fe ⊙ , respectively. We include a spread in abundance values for carbon and magnesium based on observations of their variability in nearby stars; we choose an arbitrary spread in neon abundance values… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…We used the stellar evolution code Tycho (Young & Arnett 2005) to create the catalog of evolutionary tracks discussed in detail in Truitt et al (2015) and Truitt & Young (2017), which are the basis for the model priors discussed here. The database currently contains models between 0.5-1.2 solar masses, with metallicities that fall between 0.1 − 1.5 of solar Z-value, so this is the parameter space we analyze here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the stellar evolution code Tycho (Young & Arnett 2005) to create the catalog of evolutionary tracks discussed in detail in Truitt et al (2015) and Truitt & Young (2017), which are the basis for the model priors discussed here. The database currently contains models between 0.5-1.2 solar masses, with metallicities that fall between 0.1 − 1.5 of solar Z-value, so this is the parameter space we analyze here.…”
Section: Methodsmentioning
confidence: 99%
“…Though the measurements included in Hypatia may be inherently biased due to the requirements for obtaining highresolution abundance measurements, these are stars in the solar neighborhood that give us an idea of the representative distribution of elemental compositions. We used the stellar evolution code Tycho (Young & Arnett 2005) to create the catalog of evolutionary tracks discussed in detail in Truitt et al (2015) and Truitt & Young (2017), which are the basis for the model priors discussed here. The database currently contains models between 0.5-1.2 solar masses, with metallicities that fall between 0.1 − 1.5 of solar Z-value, so this is the parameter space we analyze here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of stars on the main sequence, particularly with regards to their luminosity and effective temperature, results in a subsequent evolution of the HZ (Underwood et al 2003;Ramirez & Kaltenegger 2014). This HZ evolution has been studied within the context of stellar masses and chemical compositions (Young et al 2012;Valle et al 2014;Truitt et al 2015;Truitt & Young 2017), and also with respect to stellar rotation and magnetic activity (Gallet et al 2017). The AU Mic system provides an opportunity to study the evolution of a planetary system within the context of the early luminosity environment of the host star as it joins the main sequence.…”
Section: The Evolving Habitable Zonementioning
confidence: 99%
“…Previous work has shown that life on Earth made a detectable impact on the atmosphere after ∼1-2 Gy following the Earth's formation (Kasting et al 1993;Brocks et al 1999;Kopp et al 2005;Anbar et al 2007;Crowe et al 2013), with the Great Oxidation Event (GOE) occurring around 2 Gy following formation (Summons et al 1999;Kasting & Catling 2003;Holland 2006). Following the work of Truitt et al (2015), Truitt & Young (2017), and Truitt et al (2020), we therefore define the orbital area around a host star that will remain habitable for at least 2 Gy, here called the 2 Gy continuous habitable zone (CHZ 2 ), as a conservative estimate of the potential habitability of planets in the system across the entire main sequence. More importantly, for specific planets, it is necessary to determine whether they have already spent 2 Gy in the HZ.…”
mentioning
confidence: 99%